Stable and Ordered Body‐Centered Cubic PdCu Phase for Highly Selective Hydrogenation. Issue 3 (24th January 2023) - Li, Peicai; Liu, Xia; Guo, Mingrui; Pi, Yecan; Wang, Ning; Bai, Shuxing; Xu, Yong; Sun, Qi
Abstract: Phase engineering of nanomaterials plays a crucial role for regulating the catalytic performance. Nevertheless, great challenges still remain for elucidating the structure–selectivity correlation. Herein, this study demonstrates that the body‐centered cubic phase of PdCu ( bcc‐ PdCu) can serve as a highly active and selective catalyst for 3‐nitrostyrene (NS) hydrogenation under mild conditions. In particular, bcc ‐PdCu displays a 3‐nitro‐ethylbenzene (NE) selectivity of 93.8% with a turnover frequency (TOF) value of 4573 h −1 at 30 °C in the presence of H2 . With the assistance of NH3 ∙BH3, the selectivity of 3‐amino‐styrene (AS) reaches 94.5% with a TOF value of 13 719 h −1 . Detailed experimental and theoretical calculations reveal that improved NE selectivity is ascribed to the selective adsorption of the CC bond and desorption of NE on bcc ‐PdCu. Moreover, the presence of NH3 ∙BH3 facilitates the selective hydrogenation of NO2 due to their strong interaction and thus leads to the formation of AS. This work provides an efficient selective catalyst for NS hydrogenation under mild conditions, which may attract immediate interests in the fields of materials, chemistry, and catalysis. Abstract : This study demonstrates that the ordered body‐centered cubic phase of PdCu can serve as highly selective and active sites for 3‐nitrostyrene hydrogenation to 3‐nitro‐ethylbenzene or 3‐amino‐styrene under mild conditions. Mechanism studies reveal the different selectivity is originated from the differences in surface (catalyst)‐groups (reactants) interaction.